ENHANCING SPEAKING SKILL OF THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 2 SIGI THROUGH THE USE OF TIK TOK APPLICATION - Adinda; Mocthar, Mochtar; Patmasari, Andi; Wahyudin, Wahyudin (e-Journal of ELTS (English Language Teaching Society), 2024)
Adinda Delima Rameisyah (2024). Enhancing Speaking Skill of the Eleventh Grade Students of SMA Negeri 2 Sigi Through the Use of Tik Tok Application. English Education study program Language and Art Education Department, Teacher Training and Education Faculty, Tadulako University, under the guidance of Mochtar Marhum and Andi Patmasari. The purpose of this study to find out whether the use of the Tik Tok Application has a significant effect as a teaching tool and in enhance the speaking skills of elevents grade students at SMA Negeri 2 Sigi. This study uses a experimental class and control class. The numbers of this study were 25 students, the sample was elevents grade students at Sma Negeri 2 Sigu. Data were obtained before and after treatment, students were given a pre-test and post-test, while data were analyzed using the T-test and data obtained from the pretest and posttest were analyzed through SPSS. The results showed that there was a significant difference in students' speaking scores. Based on the sig value of the paired sample test (2-tailed) is 0.000 <0.05, meaning that Ha is accepted while Ho is rejected. It can be concluded that the use of Tik Tok Application has a significant effect on enhance the speaking skills of elevents grade students of Sma Negeri 2 Sigi.